Analisis Kriteria Penetapan Nilai Bagi Hasil Pendanaan Dengan Menggunakan Teknik ANP (Studi Kasus Pada Bank JATIM Syariah) - Lolla Rizky Nanda Devita; Dina Fitrisia Septiarini (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
The purpose of this study was to find out what is the main criteria in determining revenue sharing value of funding based on interdependence level of internal and external factors by using ANP techniques at Bank Jatim Syariah. The research method used is descriptive qualitative approach with study case method. Data collected by interviews, questionnaires, documentation and other literature. Analysis technique used is the technique of Analytic Network Process (ANP) with weighting questionnaires given to the informant. Weighting is done through comparison between the criteria, sub-criteria and sub-criteria traffic. Results from this study are the criteria of internal factors with sub criteria bank revenue of 0.17416 become a major criterion in the decision-making on determination of revenue sharing value of Funding in Bank Jatim Syariah. Results of the weighting of criteria and sub - criteria through the geometricmean of three informants of Bank Jatim Syariah.